Impact of Minimal Residual Disease Detection Prior to Autologous Stem Cell Transplantation for Post-transplant Outcome in High Risk Neuroblastoma - Bochennek, K.; Esser, R.; Lehrnbecher, T.; Glienke, W.; Wehner, S.; Erben, S.; Soerensen, J.; Schwabe, D.; Bader, P.; Klingebiel, T.; Koehl, U. (Klinische Pädiatrie, 2012)
Autologous stem cell transplantation (SCT) has become standard therapy in high risk stage IV neuroblastoma (NB) patients. Residual NB cells in the bone marrow (BM) shortly before SCT may shape the overall survival.Thus, we sought to thoroughly investigate minimal residual disease (MRD) in BM prior to SCT using conventional and real time RT-PCR for tyrosine hydroxylase (TH) as well as morphology. To avoid influence of residual NB cells in the stem cell harvest, 17 patients transplanted with MRD negative grafts (n=11 CD34-selected and n=6 unmanipulated) are included in the final analysis, only.35% of these patients are alive with a median follow up of 8.6 years. In the BM of 9/17 patients residual NB cells could be detected < 40 d before SCT. These patients had a significant lower overall survival compared to patients without BM involvement based on combined RT-PCR and morphology results (11% vs. 62%, p=0.026) or using RT-PCR, only (p=0.01). In contrast morphology on its own did not lead to a significant discrimination between both groups.Our results obtained in a small cohort of stage IV NB patients suggest that MRD diagnostic in the BM shortly before SCT might be a valuable predictive tool for these patients but requires conformation in a multicenter study.
Keywords: high risk neuroblastoma; minimal residual disease; autologous stem cell transplantation; bone marrow